Analysis of Information Technology-Based Knowledge at the Palu City Women's Empowerment and Child Protection Service - Haris abd. Kadir; Sarifuddin. T; Rasmi Nur Anggraeni; Ni Luh Liani Puspa Dewi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
This research aims to describe information technology-based knowledge at the Palu City Women's Empowerment and Child Protection Service. This research is a quantitative descriptive study with a research population of 58 people and a sample of 37 people using the Slovin formula with an error rate of 10%. The data analysis technique uses quantitative descriptive analysis with the frequency table method. As for the results obtained from Variable utilize information technology well, the indicator score value is 4.33 with interpretation (Very Good), while the results from variable Y are accepted with an average score value for the state civil servant variable of 4.36, so it can be seen that the existing resources The Palu City Women's and Children's Empowerment Service is excellent and can be used for agency development because the responsibilities and performance produced by employees are practical and efficient, with the indicator score obtained being 4.36 with an interpretation of (Very Good), with research results showing that information technology-based knowledge has been implemented at the Palu City Women's Empowerment and Child Protection Service.